Hard Tick Species of Livestock and their Bioecology in Golestan Province, North of Iran. - Aioub Sofizadeh; Zakkyeh Telmadarraiy; Abbas Rahnama; Ahmad Gorganli-Davaji; Asadollah Hosseini-Chegeni (Tehran University of Medical Sciences, 2014)
Background: A survey on tick species composition was carried out in Golestan Province Iran during year 2010-2011.The aim was to determine tick species parasitizing domestic ruminants and their seasonal population dynamics. Methods: A total of 124 sheep, 92 goats, 84 cattle, 74 camels and 12 horses in several villages were inspected for tick infestation. The collected ticks preserved in 70% alcohol and then were identified. Results: The overall 1059 ticks (453 female, 606 male) were collected. The ticks occur on sheep, goats, cattle, cam- els and horses as 72.1%, 77.3%, 75.8%, 69.3%, and 50% respectively. The frequency of ticks in spring was more than other seasons and the least was observed in winter. In the spring and summer, infestation rate in domestic rumi- nants  were  calculated as  100%.  Six  genus  and  fourteen  hard  and  soft  tick  species  were  identified including Rhipicephalus sanguineus, R. bursa, Ixodes ricinus, Haemaphysalis punctata, H. sulcata, H. erinacei, H. inermis, Hyalomma marginatum, Hy. asiaticum, Hy. dromedarii, Hy. excavatum, Hy. anatolicum, Hy. detritum, Boophilus annulatus and Argas persicus. Rhipicephalus sanguineus was the most abundant species in the study area. The larg- est  number of ticks  was collected from animal ears and  tails.  Haemaphysalis, Hyalomma, Rhipicephalus and Boophilus occurred in mountainous, forest and plateau areas of Golestan Province but Ixodes occurred only in mountainous and forest areas, whereas Rhipicephalus and Hyalomma were present in coastal areas of Golestan Province. Conclusion: The result of this study is a survey on tick species from domestic animals in Iran and implication of possible prevention measures for diseases transmitted by ticks.